SARS-CoV-2 pharmacologic therapies and their safety/ effectiveness according to level of evidence (2020)
Introduction: There is a pressing need for COVID-19 transmission control and effective treatments. We aim to evaluate the safety and effectiveness of SARS-CoV-2 pharmacologic therapies as of August 2, 2020 according to study level of evidence. Methods: PubMed, ScienceDirect, Cochrane Library, JAMA Network and PNAS were searched. The following keywords were used: ((COVID-19) OR (SARS-CoV-2)) AND ((((((therapeutics) OR (treatment)) OR (vaccine)) OR (hydroxychloroquine)) OR (antiviral)) OR (prognosis)). Results included peer-reviewed studies published in English. Results: 15 peer-reviewed articles met study inclusion criteria, of which 14 were RCTs and one was a systematic review with meta-analysis. The following pharmacologic therapies were evaluated: chloroquine (CQ), hydroxychloroquine (HCQ), antivirals therapies, plasma therapy, anti-inflammatories, and a vaccine. Conclusion: According to level 1 evidence reviewed here, the most effective SARS-Co-V-2 pharmacologic treatments include remdesivir for mild to severe disease, and a triple regimen therapy consisting of lopinavir-ritonavir, ribavirin and interferon beta-1b for mild to moderate disease. Also, dexamethasone significantly reduced mortality in those requiring respiratory support. However, there is still a great need for detailed level 1 evidence on pharmacologic therapies.